A unified model of shared brain structural alterations in patients with different mental disorders who experience own‐thought auditory verbal hallucinations—A pilot study. Issue 6 (18th April 2020) - Zhuo, Chuanjun; Wang, Chunxiang; Song, Xueqin; Xu, Xuexin; Li, Gongying; Lin, Xiaodong; Xu, Yong; Tian, Hongjun; Jiang, Deguo; Wang, Wenqiang; Zhou, Chunhua
Abstract: Objective: To explore shared brain structural alterations in patients diagnosed with mental disorders who experience own‐thought auditory verbal hallucinations (OTAVHs). Methods: A cohort of 143 first‐diagnosis, nonmedicated patients with OTAVHs was enrolled: 25 with schizophrenia (FUSCH‐OTAVH), 20 with major depression disorder (FUMDD‐OTAVH), 28 with bipolar disorder (FUBD‐OTAVH), 22 patients with posttraumatic stress disorder (FUPTSD‐OTAVH), 21 with anxiety disorder (FUAD‐OTAVH), and 27 with borderline personality disorder (FUBPD‐OTAVH); 25 healthy controls (HCs) participated. The Auditory Hallucinations Rating Scale (AHRS), multiple psychometric scales, voxel‐based morphometry (VBM), tract‐based spatial statistics (TBSS), and multiple regression were used. Results: Compared with HCs, patients had increased occipital cortex, dorsal prefrontal cortex (PFC), and striatum gray matter volumes (GMVs), a reduced insular cortex (IC) GMV, and an impaired frontooccipital fasciculus. The following differences were found versus HCs: FUSCH‐OTAVH, reduced PFC and occipital GMVs, increased striatum and thalamus GMVs, impaired arcuate fasciculus, u‐shaped bundle, optic tract, and upper longitudinal fasciculus (LF); FUMDD‐OTAVH, increased posterior frontotemporal junction and hippocampus GMVs; FUMN‐OTAVH, increased posterior frontotemporal junction and parietal cortex GMVs, reduced hippocampus GMV, impaired upper LF; FUPTSD‐OTAVH, increased temporal, hippocampus, and nucleus accumbens GMVs; FUBPD‐OTAVH, increased frontotemporal junction and hippocampus GMVs, impaired upper/lower LF; and FUAD‐OTAVH, increased frontal and temporal cortex, hippocampus GMVs. Conclusions: The present findings provide evidence consistent with a bottom‐up and top‐down reciprocal action dysfunction hypothesis of AVHs and with the dopamine hypothesis of AVHs. We observed specific features related to OTAVHs in patients with different mental disorders. The findings, though complex, provide clues for further studies of specific mental disorders. Abstract : We observed an unified model of shared brain structural alterations in patients with different mental disorders who experience own‐thought auditory verbal hallucinations. These findings support a unified model of own‐thought auditory verbal hallucinations.